Depth of Cervical Intraepithelial Neoplasia Grade 3 in Peruvian Women: Implications for Therapeutic Depth of Necrosis. Issue 1 (January 2018) - Taxa, Luis; Jeronimo, Jose; Alonzo, Todd A.; Gage, Julia; Castle, Philip E.; Cremer, Miriam L.; Felix, Juan C.
Abstract : Objective: To determine the involvement of cervical intraepithelial neoplasia grade 3 (CIN3) in a population of women in a lower-resource setting. Methods: One hundred twelve consecutive cone excision specimens with histological diagnosis of CIN3 were retrieved from the National Institute of Neoplastic Diseases in Lima Peru. Two pathologists independently evaluated each specimen microscopically and confirmed 107 cases that could be measured by optical micrometry. Depth and breadth of the lesions were measured microscopically. Results: The mean maximal depth of cervical involvement by CIN3 was 2 ± 0.13 mm; depth was less than 3.5 mm in 89.7% of cases and less than 5 mm in 93.5%. Mean breadth of CIN3 was 7.3 ± 4.4 mm; breadth was less than 15.9 mm in 95% of cases and less than 20.5 mm in 99.7%. The correlation coefficient between breadth and depth of CIN3 was 0.61. No significant correlation was found between age and depth. Conclusions: Depth of CIN3 involvement in a developing country is significantly deeper than that reported in the United States. Treatment selection for women with CIN3 and risk of treatment failure may vary between developing and developed countries because of the difference in the depth of lesions. Countries with underscreened populations need to consider the increased disease severity in devising treatment strategies. Abstract : Pathological analyses of CIN3 specimens from a population in a developing country reveal significantly deeper involvement than those reported in high-income settings.